Determination of genetic diversity of the Akkaraman sheep breed from Turkey - Ozmen, Ozge; Kul, Selim; Gok, Taskin (Elsevier, 2020)
According to archaeological and genetic research, Turkey is a major sheep domestication center. Akkaraman has the largest population among the sheep breeds of Turkey, and until now, the Akkaraman breed has only been categorized as type based on morphological similarities. In the present study, Akkaraman types (Karakas, Kangal, and Savak) were assessed for the first time for their genetic structure and relationship with other sheep breeds (Morkaraman, Awassi, and Norduz) living in the same area using 29 microsatellite loci. A total of 594 animals were genotyped for genetic characterization. According to results, Akkaraman types (Karakas, Kangal, and Savak) were distinguished from each other based on microsatellite loci information. We determined that Savak-Akkaraman sheep have distinct genotypes, which most likely resulted from the effects of different breeding histories, geographic distributions, ecological factors, or the effects of selection. This is the first report on the genetic diversity of Akkaraman sheep varieties, and the data generated by this research could be useful to constitute a source for sustainable development of genetic resources and conservation activities to avoid losses of world livestock genetic heritage.
Keywords: Ovis aries; Sheep type; Genetic differentiation; Microsatellites